Microfinance impact on women's decision making: a case study of Andhra Pradesh - Vachya Lavoori; Rajendra Paramanik (Journal of Global Entrepreneurship Research, 2014)
The present study seeks to examine the impact of microfinance and other socio-economic factors on women empowerment as viewed from their participation in decision making, income as well as employment generation activities. The findings of the study based on a field study conducted in two villages of Andhra Pradesh suggest that factors such as member and her husband's income, family size and frequency of Self help group meetings have overall positive influence on women empowerment. In case of income and employment generation activities, age and income of Self help group members, their household income and amount of loan are found to have positive effect.
Keywords: D20; G34; L10; 650; Microfinance; Self help group-bank linkage program; Income/employment generation and women decision making